Community pharmacists' roles, attitudes and knowledge regarding provision of screening and brief intervention activities for alcohol use in Catalonia. (14th February 2023) - Torres‐Novellas, Berta; Palacio‐Vieira, Jorge; Segura‐García, Lidia; Díaz, Estela; Rius, Pilar; Veciana, Antonio; Colom, Joan
Abstract: Introduction: Community pharmacists (CP) are among the health professionals with closest contact to the general population. They play a key role in delivering public health programs. The aim of this study was to analyse the attitudes, knowledge, preparedness and ability to screen and advise on alcohol of CP in Catalonia and their perceptions about the provision of alcohol screening and brief interventions (SBI) in community pharmacies. Methods: This is an observational, cross‐sectional study. An online survey on attitudes, knowledge and behaviours was sent to all registered CP in Catalonia, and bivariate and multivariate statistical analyses were conducted. Results: The response rate was 7.96% (639/8027), more than two‐thirds of respondents were 41 years of age or older and 79.9% were female. Results showed that CP readiness to offer advice on alcohol problems was higher than their preparedness to screen (37.5% vs. 31.8%, respectively). They also showed that having received 1 h or more of training on alcohol and drug‐related health promotion and prevention during the last 5 years increased CP perception of role security and therapeutic commitment related to alcohol. Discussion and Conclusion: This study showed that involving CP in the provision of alcohol SBIs may be feasible in Catalonia. Furthermore, this and previous research show an association between CP training in alcohol or drugs and preparedness to screen and advise on alcohol use. Consequently, promoting alcohol‐related training programs to enhance CP skills is recommended to support successful implementation of alcohol SBI in community pharmacy settings.